2023
DOI: 10.3389/fpsyg.2022.1095111
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation improves frontal lobe cognitive functions and mental health of older adults with non-amnestic mild cognitive impairment: Case studies

Abstract: IntroductionThis study investigated the effects of transcranial photobiomodulation (tPBM) on improving the frontal lobe cognitive functions and mental health of older adults.MethodsThree older adults with mild cognitive impairment (MCI) of the non-amnestic type received 18-session tPBM stimulation for 9 weeks and were assessed with neuropsychological tests of memory and executive functions and standardized questionnaires on depressive and anxiety symptoms, global cognitive functions, and daily functioning abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…For example, Salehpour et al 's meta-analysis found that tPBM can have beneficial effects on memory, attention, and executive function in healthy individuals (Salehpour et al, 2019). Furthermore, meta-analysis studies that focused on patients with MCI, dementia, stroke, Parkinson's and Alzheimer's disease, also found that tPBM was beneficial to promote recovery of cognitive function (Spera et al, 2021;Cheung et al, 2023;Kuo and Kim, 2023;McGee et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Salehpour et al 's meta-analysis found that tPBM can have beneficial effects on memory, attention, and executive function in healthy individuals (Salehpour et al, 2019). Furthermore, meta-analysis studies that focused on patients with MCI, dementia, stroke, Parkinson's and Alzheimer's disease, also found that tPBM was beneficial to promote recovery of cognitive function (Spera et al, 2021;Cheung et al, 2023;Kuo and Kim, 2023;McGee et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been shown in healthy young people and seniors, describing positive effects on their cognitive mechanism after PBM application. Specifically, cognitive skills activated in the frontal lobe were enhanced focusing on working memory, cognitive flexibility, sustained attention, inhibitory ability, executive function in general, and rule-based learning (Rojas, & Gonzalez-Lima, 2016;Lee et al, 2022;Cheung et al, 2023).…”
Section: Use Of Transcranial Photobiomodulation (Tpbm) In Asdmentioning
confidence: 99%